CB2 and TRPV1 receptors oppositely modulate in vitro human osteoblast activity. (September 2015) - Rossi, Francesca; Bellini, Giulia; Tortora, Chiara; Bernardo, Maria Ester; Luongo, Livio; Conforti, Antonella; Starc, Nadia; Manzo, Iolanda; Nobili, Bruno; Locatelli, Franco; Maione, Sabatino
Graphical abstract: Abstract: In the current study, we have investigated the effect of CB2 and TRPV1 receptor ligands on in vitro osteoblasts from bone marrow of human healthy donors. A pivotal role for the endocannabinoid/endovanilloid system in bone metabolism has been highlighted. We have demonstrated a functional cross-talk between CB2 and TRPV1 in human osteoclasts, suggesting these receptors as new pharmacological target for the treatment of bone resorption disease as osteoporosis. Moreover, we have shown the presence of these receptors on human mesenchimal stem cells, hMSCs. Osteoblasts are mononucleated cells originated from hMSCs by the essential transcription factor runt-related transcription factor 2 and involved in bone formation via the synthesis and release of macrophage colony-stimulating factor, receptor activator of nuclear factor kappa-B ligand and osteoprotegerin. For the first time, we show that CB2 and TRPV1 receptors are both expressed on human osteoblasts together with enzymes synthesizing and degrading endocannabinoids/endovanilloids, and oppositely modulate human osteoblast activity in culture in a way that the CB2 receptor stimulation improves the osteogenesis whereas TRPV1 receptor stimulation inhibits it.